Elderly Patient Management Problems: Antithrombotic Therapy Selection Features. Clinical Case - D. U. Akasheva; E. S. Bulgakova; I. S. Yavelov; A. Yu. Gorshkov; O. M. Drapkina (Рациональная фармакотерапия в кардиологии, 2018)
The growing population of elderly people is the main «antithrombotic drugs consumer» because there is higher prevalence of thromboembolic diseases (acute coronary syndrome, venous thromboembolism, atrial fibrillation) among them than among younger people. Elderly people have high risks of both thromboembolic and bleeding complications associated with antithrombotic drugs using. Antithrombotic drug choice is based on individual careful estimation of the «risk/benefit» ratio. Sometimes real clinical practice gives us problems and questions, having no answers in any guidelines. Such a difficult clinical case of elderly patient management is presented in this article.